Ovarian Function Suppression With Luteinizing Hormone-Releasing Hormone Agonists for the Treatment of Hormone Receptor-Positive Early Breast Cancer in Premenopausal Women - Lu, Yen-Shen; Wong, Andrea; Kim, Hee-Jeong (Frontiers in Oncology, 2021)
Chemotherapy and endocrine therapies are mainstays of treatment for early and advanced hormone receptor-positive (HR+) breast cancer. In premenopausal women with HR+ tumors, the benefits of adding ovarian function suppression (OFS) to endocrine therapy have been debated. Consequently, for many years, tamoxifen monotherapy has been the standard of care for endocrine treatment in the adjuvant setting. Recent studies have, however, provided new evidence that, in some premenopausal patients, OFS in combination with tamoxifen or aromatase inhibitors (AIs) can significantly increase survival versus tamoxifen alone. Luteinizing hormone releasing hormone agonists (LHRHa), including goserelin, triptorelin, and leuprorelin, achieve OFS through sustained suppression of the release of follicle-stimulating hormone and luteinizing hormone from the pituitary. In turn, this suppresses production and secretion of estradiol, an ovarian hormone that supports cancer cell growth, survival, and proliferation. In this review, we discuss the clinical evidence supporting the addition of LHRHa to adjuvant endocrine therapies, including tamoxifen and AIs, for premenopausal women with breast cancer. We also discuss the role of LHRHa use in combination with adjuvant chemotherapy to preserve ovarian function and fertility in young patients with breast cancer. Finally, we discuss important practical aspects of the use of LHRHa in breast cancer treatment, including side-effects, patient adherence to treatment and the use of slow-release, long-acting drug formulations.